Memahami Kompleksitas Tata Kelola dalam Pengawasan Keamanan Maritim: Analisis Enam Dimensi dari Polairud Polda Gorontalo - Nur Fadli Umar; Yanti Aneta; Juriko Abdussamad; Yakob Noho Nani; Muchlis Akuba (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
This study examines the complexity of governance in maritime security surveillance conducted by the Gorontalo Regional Police's Water and Air Police (POLAIRUD). Maritime security surveillance involves multiple institutions with overlapping authorities, making effective coordination essential to address increasingly dynamic maritime threats. Drawing on Governance Complexity Theory, this study explores six dimensions shaping the maritime surveillance system: interdependence, actor diversity, uncertainty, dynamic interactions, network coordination, and adaptation and learning. A qualitative case study approach was employed through in-depth interviews, field observations, and document analysis involving relevant stakeholders. The findings indicate that maritime surveillance operates within a complex governance environment where information, authority, and operational resources are distributed across multiple actors. The effectiveness of surveillance is influenced not only by organizational capacity but also by the ability to establish collaborative networks, manage uncertainty, share information efficiently, and adapt to evolving maritime conditions. Furthermore, successful maritime security governance depends on continuous communication, institutional flexibility, and collective learning among stakeholders to respond to emerging security challenges. The study demonstrates that maritime security governance is inherently relational and adaptive, requiring collaborative arrangements that extend beyond conventional hierarchical structures. These findings contribute to the development of governance complexity literature by providing empirical evidence from the Indonesian maritime security context and emphasizing the importance of network-based, adaptive, and integrated governance mechanisms in strengthening maritime surveillance and supporting sustainable maritime security management.